A Combinatorics Course with One Goal: Authentic Mathematical Inquiry. Issue 2 (7th February 2017) - Storm, Christopher
Abstract: This article shares an example of a course in Combinatorics, taught at Adelphi University in Fall 2012, designed with a primary goal of engaging students in pursuing mathematics as mathematicians do. The course went beyond usual applications of inquiry-based learning in that students were also charged with the responsibility of posing the mathematical statements that would be examined as part of the course. In this way, students decided what was interesting to study and were responsible for the creation of mathematics within their classroom community. This article looks at the syllabus policies for the course, describes some of the work that students did as part of the course, and reflects upon the outcomes of the course.